Dealkylation of isopropylbenzene on 7-lrradiated silíca-alumina. The effect of various reagents on the active centers and on their yield - Rojo, Enrique Aldo; Hentz, Roberto R. (American Chemical Society, 1972)
Fil: Rojo, Enrique Aldo Comisión Nacional de Energía Atómica; Argentina